2016
DOI: 10.1007/s11154-016-9344-5
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the metabolic and health effects of low-calorie sweeteners: methodological considerations and implications for future research

Abstract: Consumption of foods, beverages, and packets containing low-calorie sweeteners (LCS) has increased markedly across gender, age, race/ethnicity, weight status, and socioeconomic subgroups. However, well-controlled intervention studies rigorously evaluating the health effects of LCS in humans are limited. One of the key questions is whether LCS are indeed a beneficial strategy for weight management and prevention of obesity. The current review discusses several methodological considerations in the design and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 70 publications
(109 reference statements)
0
33
0
2
Order By: Relevance
“…Although artificial sweeteners are marketed as healthy alternatives for consumers seeking to avoid sugar-containing products (de la Pena 2010), several studies have shown a positive correlation between weight gain and consumption of such products (Stellman and Garfinkel 1988; Fowler et al 2008). However, the effects of artificial sweeteners remain controversial as results appear to be somewhat dependent on experimental conditions (Sylvetsky et al 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Although artificial sweeteners are marketed as healthy alternatives for consumers seeking to avoid sugar-containing products (de la Pena 2010), several studies have shown a positive correlation between weight gain and consumption of such products (Stellman and Garfinkel 1988; Fowler et al 2008). However, the effects of artificial sweeteners remain controversial as results appear to be somewhat dependent on experimental conditions (Sylvetsky et al 2016). …”
Section: Discussionmentioning
confidence: 99%
“…68 All were relatively short in duration, and the majority were conducted as part of multifaceted weight loss programs in obese individuals, which does not address routine consumption of nonnutritive sweeteners by healthy individuals. In addition, some trials evaluated nonnutritive sweeteners in capsule form, which may alter their physiologic effects, while others were subject to potential bias from lack of blinding and industry sponsorship.…”
Section: Limitationsmentioning
confidence: 99%
“…Given the ongoing controversy surrounding the role of LCSs in weight management and chronic disease, we recently highlighted several key methodologic issues (4), including the need to correctly categorize LCS exposure of clinical study volunteers and to take this information into account when interpreting study findings. Recent data show that w25% of children and 40% of adults in the United States consume foods, beverages, or packets [e.g., Splenda (Heartland Consumer Products) or Equal (Merisant Company), often added to tea and coffee as sugar substitutes] containing LCSs (5).…”
Section: Introductionmentioning
confidence: 99%